BlueHarvest: Enhancing Indonesian Aquaculture with a Market-Driven UI/UX Design - Dermawan, Andi; Aziza, Rifda Faticha Alfa (Journal of Information Systems and Informatics, 2025)
This research aims to design the user interface (UI) and user experience (UX) of an aquaculture marketplace application to improve the promotion and marketing of Indonesian fishery products through an application called “BlueHarvest”. Using the double diamond method, this research explored the needs of expert and non-expert users in the field of aquaculture to create an attractive and intuitive solution. The research started with surveys and interviews to collect in-depth data visualized in empathy maps and user journeys, which revealed key user-centric features such as a dynamic price dashboard to know real-time market trends, a pond monitoring system to help fishermen and buyers, and offering articles on aquaculture as well as aquaculture product recommendations. Usability testing results showed that the app design was generally easy to understand, although there were some suggestions to improve the icons, layout and search filter features. These findings indicate that the applied design approach successfully built a solid user experience foundation, although further refinements are needed for optimal usability.